3047 Patient-Reported Outcomes Measurement Information System (PROMIS®) Global Health Short Form is Responsive to Patient Reported Changes in Systemic Lupus Erythematosus. (27th March 2019) - Kasturi, Shanthini; Szymonifka, Jackie; Berman, Jessica; Kirou, Kyriakos; Levine, Alana; Sammaritano, Lisa; Mandl, Lisa
Abstract : OBJECTIVES/SPECIFIC AIMS: The accurate and efficient serial measurement of patient centered outcomes is a priority in the clinical care of systemic lupus erythematosus (SLE). Patient-Reported Outcomes Measurement Information Systems (PROMIS®) Global Health Short Form (PROMIS10) is a 10-item universal patient reported outcome measure of global physical and mental health with construct validity in SLE. The longitudinal responsiveness (sensitivity to change) of PROMIS10 in SLE patients is unknown. We aimed to evaluate the responsiveness of PROMIS10 in SLE outpatients using patient and physician-derived anchors. METHODS/STUDY POPULATION: Adults meeting SLE classification criteria were recruited from an SLE Center of Excellence. Subjects completed PROMIS10 at two visits a minimum of one month apart. SLE disease activity was measured with a patient global assessment of change, a physician global assessment and the physician-derived SELENA-SLEDAI. Responsiveness over time of PROMIS10 scores was evaluated using known-groups validity. Effect sizes of changes in PROMIS global physical health and global mental health scores from baseline to follow up were compared across groups of patients who differed in their patient global assessment of change, physician global assessment, and SELENA-SLEDAI using Kruskal-Wallis tests. RESULTS/ANTICIPATED RESULTS: A diverse cohort of 228 SLE patients completed baseline surveys (Table 1), with 190 (83%) completing a follow up survey. Using the patient-based anchor, PROMIS10 demonstrated mild to moderate responsiveness to improvement (effect size 0.29) and worsening (effect sizes −0.27 and −0.54) of health status for both global physical health and global mental health (Table 2). Using the physician global assessment and SELENA-SLEDAI as anchors, there were no statistically significant differences in effect sizes across groups. DISCUSSION/SIGNIFICANCE OF IMPACT: PROMIS10 showed responsiveness over time to patient-reported, but not physician-derived changes in lupus health status. These data suggest that PROMIS10 can be used to efficiently measure and monitor important aspects of the patient experience of lupus not captured by physician-derived metrics. Further studies are needed to evaluate the role of PROMIS in optimizing longitudinal disease management in SLE.